1983
DOI: 10.1161/01.cir.67.2.310
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sensitivity of exercise, cold pressor and ergonovine testing in provoking attacks of variant angina in patients with active disease.

Abstract: SUMMARY Exercise, ergonovine and the cold pressor test have been used to provoke variant angina attacks. The sensitivity of these three tests was compared in 34 hospitalized patients with well documented, active variant angina who had recently undergone coronary arteriography. The three tests were usually perfornmed on three consecutive days, and 28 of the 34 Methods Patient PopulationThe following criteria were required for the diagnosis of variant angina: burning or squeezing retrosternal chest pain at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(49 citation statements)
references
References 30 publications
1
47
0
1
Order By: Relevance
“…The first observation is consistent with the findings of a recent report, showing only a 10% incidence of positive results of the cold pressor test in a group of 34 patients with variant angina, 32 of whom (94%) responded to ergonovine. 26 We certainly cannot exclude that in our patients a-stimulation could have produced minor degrees of coronary vasoconstriction, insufficient to cause ST segment changes, as described in two patients by Raizner et all However, this possibility appears rather unlikely, at least in the eight patients with coronary lesions equal or greater than 90% in whom even minimal changes in coronary cross-sectional area should be critical enough to produce acute myocardial ischemia. Although coronary spasm can be undoubtedly precipitated in some patients with very active disease by various sympathetic maneuvers, the reproducibility and specificity of this response have not yet been assessed and its actual relevance to the pathophysiologic mechanism of coronary spasm has not been demonstrated.…”
Section: Discussionmentioning
confidence: 71%
“…The first observation is consistent with the findings of a recent report, showing only a 10% incidence of positive results of the cold pressor test in a group of 34 patients with variant angina, 32 of whom (94%) responded to ergonovine. 26 We certainly cannot exclude that in our patients a-stimulation could have produced minor degrees of coronary vasoconstriction, insufficient to cause ST segment changes, as described in two patients by Raizner et all However, this possibility appears rather unlikely, at least in the eight patients with coronary lesions equal or greater than 90% in whom even minimal changes in coronary cross-sectional area should be critical enough to produce acute myocardial ischemia. Although coronary spasm can be undoubtedly precipitated in some patients with very active disease by various sympathetic maneuvers, the reproducibility and specificity of this response have not yet been assessed and its actual relevance to the pathophysiologic mechanism of coronary spasm has not been demonstrated.…”
Section: Discussionmentioning
confidence: 71%
“…45 For patients with coronary artery spasm, this may be elicited by stressing with intravenous ergonovine maleate. 44 The design of this study did not include preoperative Holter monitoring. We cannot say whether these ST changes were totally new in relation to the preoperative stress, or whether they were a progression of preoperative events.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with variant angina or CSA, 37.8% to 67.5% of patients had positive ischemic findings as shown in Table 1. Organic stenosis was found in 14.7% to 74.6% of these patients [15,[20][21][22]. Table 2a showed that more than a third patient with CSA and without organic stenosis had ischemic findings on exercise tests, while more than two thirds patients with CSA with organic stenosis had ischemic findings on exercise testing as shown in Table 2b.…”
Section: Treadmill Exercise Testsmentioning
confidence: 94%
“…Positive rate by cold pressor test was 14% to 15% of patients with variant angina, as shown in Table 1 [3,21]. Some cardiologists performed the combined cold pressor and hyperventilation test in patients with variant angina.…”
Section: Combined Cold Pressor and Hyperventilation Testmentioning
confidence: 96%